Microelectrical mechanical systems switch for designing multi-band antenna - Alam, A. H. M. Zahirul; Islam, Md. Rafiqul; Khan, Sheroz; Rashid, Muhammad Mahbubur (Science Publications, 2009)
Problem statement: In this study Microelectrical Mechanical System (MEMS) switches were proposed to design a reconfigurable/multi-band antenna to replaced PIN diode switches or semiconductor switches due to lower insertion losses, good isolation, much lower intermodulation distortion, and lower power consumption. The antenna is able to operate at very high frequencies. Approach: A reconfigurable antenna that is capable to operate at several frequencies was proposed by introducing two adjacent patches along with main radiating patch and two MEMS switches. Parametric done for Alumina, SiN, GaAs and Teflon as MEMS bridge materials for finding better results in terms of return loss and number of bands. The design was performed by using 3D electromagnetic simulator HFSS considering ideal MEMS switches. Results: It was found that SiN as MEMS bridge material 21.91 GHz in the "ON" states of MEMS switches. Conclusion/Recommendations: MEMS cantilever beam material played an important role for providing antenna to operate at multi-band frequencies. The proposed multiband/reconfigurable antenna can be implemented with easy fabrication process steps by the Sandwich method of fabrication.